2021
DOI: 10.1126/science.abg2365
|View full text |Cite
|
Sign up to set email alerts
|

Lack of transgenerational effects of ionizing radiation exposure from the Chernobyl accident

Abstract: Effects of radiation exposure from the Chernobyl nuclear accident remain a topic of interest. We investigated whether children born to parents employed as cleanup workers or exposed to occupational and environmental ionizing radiation post-accident were born with more germline de novo mutations (DNMs). Whole-genome sequencing of 130 children (born 1987-2002) and their parents did not reveal an increase in the rates, distributions, or types of DNMs versus previous studies. We find no elevation in total DNMs reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…The study of cancer incidence in children born to the A-bomb survivors in Hiroshima and Nagasaki has not found a link to parental radiation exposure doses [14]. The genetic study found no evidence of elevated rate of germline de novo mutations (that theoretically might contribute to transgenerational health effects) in children of parents exposed following the Chernobyl accident in Ukraine [15]. Therefore, the increased incidence of thyroid cancer in Belarus in non-exposed children is unlikely due to radiation factor or possible exposures, if any, of their parents.…”
Section: Introductionmentioning
confidence: 97%
“…The study of cancer incidence in children born to the A-bomb survivors in Hiroshima and Nagasaki has not found a link to parental radiation exposure doses [14]. The genetic study found no evidence of elevated rate of germline de novo mutations (that theoretically might contribute to transgenerational health effects) in children of parents exposed following the Chernobyl accident in Ukraine [15]. Therefore, the increased incidence of thyroid cancer in Belarus in non-exposed children is unlikely due to radiation factor or possible exposures, if any, of their parents.…”
Section: Introductionmentioning
confidence: 97%
“…However, new signatures are still being discovered by analyzing genomes of healthy cells as well as cancer ( Pleguezuelos-Manzano et al, 2020 ; de Kanter et al, 2021 ; Gurjao et al, 2021 ). An example of using somatic mutation data to assess cancer risk in exposed humans , is the recent study on Chernobyl survivors ( Morton et al, 2021 ; Yeager et al, 2021 ). In these studies, the mutagenic effects of ionizing radiation could be observed in papillary thyroid carcinoma, but no transgenerational germline de novo mutations could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence has been found for increased cancer incidence among the children of fathers who were exposed to those blasts [65][66][67]. Moreover, there is a recent report that shows no genetic effects of radiation in people exposed to the 1986 Chernobyl nuclear accident [68]. Furthermore, in clinical practice, a Danish case-cohort study demonstrated that mutagenic chemotherapy and radiotherapy doses delivered to the gonads were not associated with genetic defects in the children of cancer survivors, although larger studies must be conducted to explore in greater depth the potential associations between high-dose pelvic irradiation and specific adverse pregnancy outcomes [69].…”
Section: Human Epidemiological Datamentioning
confidence: 99%